The Life of Jesus According to Paul - Viktor KALASHNIKOV (Богословські роздуми: Східноєвропейський журнал богословʼя)
It is widely accepted in modern biblical scholarship that Paul has little interest in the historical Jesus because he rarely refers to the events of Jesus’ life. The British evangelical scholar, David Wenham, has recently challenged this assumption in his Paul: Follower of Jesus or Founder of Christianity?  Wenham claims that Paul’s allusions to the life of Jesus are more numerous than what appears on the text’s surface. Has Wenham succeeded in his reevaluation of the data? This is the central question of the present article. Having analyzed Wenham’s arguments in detail, the author concludes that the new hypothesis does not stand the test. In his judgment, Paul’s silence regarding the ministry of Jesus remains undeniable. Yet, this silence is not to be taken as an argument against the historical reliability of the Gospel accounts. Rather, it points to the literary distinction between the gospels and the epistles, as well as to certain distinctive features of Paul’s theology.